Loading on the Upper Limb in the Tennis Serve - Elliott, B. (2002)
Orthopaedic surgeons, sport physicians, physiotherapists, sport scientists and trainers who understand the mechanical basis of stroke production are better able to administer effective preventative and rehabilitation programs. Professional tennis bas placed an ever increasing demand on the body. Upper limb (primarily the shoulder) and back injuries are more common than injuries to the lower extremity for high performance players4 and so these will be discussed in this presentation. A) Eccentric loading: As the hitting shoulder is driven upward the racket is displaced "away from and behind" the back and the upper arm is forced into a position of maximal external rotation. Male players achieved higher service speeds (183 km hr-1 than females (149 km hr-1 at the Sydney 2000 Olympics. This was achieved by recording larger internal rotation torque at maximal external rotation (male = 64.9 Nm, female = 37.5 Nm).3 A higher elbow varus torque (67.6 Nm) was also recorded at maximal external rotation, when compared with female counterparts (41.3 Nm). Eccentric loading during this action may lead to injury. B) Peak loading in the forward swing: Peak internal rotation torques were relatively high for both sexes (males = 71 Nm and females = 48 Nm), which supports the importance of internal rotation in the service action. There was a trend for peak varus torque to be higher for males (78 Nm) when compared with the females (58 Nm). C) The use of co-ordinated movement of body segments in velocity generation. The absence of one segment means that other segments must "make-up" for this loss. Disruption to the kinetic chain has been proposed as one reason for increased joint loading.4 D) The development of trunk angular momentum: The importance of trunk, end-over-end and forward rotations, are integral parts of high velocity serving.1 Matsuo et al.5 in baseball showed that a shoulder angle of ~100° produced the highest ball velocity and the lowest shoulder and elbow loading in pitching. Conclusions Dillman et al.2 stated that any torque greater than 50 Nm in the upper extremity was a significant factor in loading that area of the body. This level was achieved for both shou1der and elbow joints at different phases of the service action. It is therefore apparent that the upper limb is subject to high loads during the service action, and this movement if repeated many times, may have the potential to cause injury.